Social Mobility In Shaw's Arms And The Man (1894):A Marxist Analysis - Gintarani, Tigar Gumilang Tian (2017)
This study is about how social mobility is reflected in George Bernard Shaw's Arms and the Man playwright. The aim of this study is to describe the indicators of the social mobility, to analyze the depiction of social mobility, and to reveal the reason why Shaw illustrated the social mobility in his play. In analyzing this play, the researcher uses the Marxist perspective and the qualitative method. The study comes to the following conclusions. Firstly, there are three indicators of social mobility i.e. occupational, property and authority structure. Secondly, the depiction of the social mobility is depicted through the plot and characters of the play. Thirdly, the reason why the author writes the play is to criticize about the society in that era. He wants to awaken the public opinion about the social problem in their environment.